Comparison of Different Waves during the COVID-19 Pandemic: Retrospective Descriptive Study in Thailand. (8th October 2021) - Kunno, Jadsada; Supawattanabodee, Busaba; Sumanasrethakul, Chavanant; Wiriyasivaj, Budsaba; Kuratong, Sathit; Kaewchandee, Chuthamat
Abstract : Background . Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. An outbreak is called an epidemic when there is a sudden increase in cases. Many countries have experienced a two-wave pattern in the reported cases of COVID-19. The spread of COVID-19 in Thailand was a cluster event distributed over multiple locations. This study aims to compare the characteristics of different waves during the COVID-19 pandemic in Thailand. Methods . A retrospective cohort study was conducted from January 2020 to May 2021 (17 months) to determine the number of COVID-19 screenings and confirmed cases and deaths as well as sociodemographic characteristics such as gender, age, nationality, and source population at risk factors. The categorical data were compared using a chi-square test. Results . Three waves of the COVID-19 pandemic occurred within 17 months in Thailand, and the number of cases increased by over 100, 000 due to source population at risk factors such as close contact with a previously confirmed patient, community risk, cluster communities, and active and community surveillance. The chi-square test revealed significant differences between the three waves (p < 0.01 ). Conclusion . Significant differences between pandemic phases or waves may be due to weak social distancing policies and the lack of public health interventions. A COVID-19 vaccination plan is needed for people at risk of suffering severe symptoms and the general population in outbreak areas to increase immunity.